Intradentinal antimicrobial action and filling quality promoted by ultrasonic agitation of epoxy resin-based sealer in endodontic obturation (Journal of Applied Oral Science, 2017)
The aim of this study was evaluate the influence of ultrasonic activation (UA) of AH Plus to improve canal and isthmus filing, and analyse the antimicrobial effect against Enterococcus faecalis within dentinal tubules. Material and Methods: Thirty mesial roots of mandibular first molars were selected and divided into 2 groups (n = 15): with and without UA of the sealer. Then the root canals were filled by using the single cone technique, and the specimens were sectioned at 2, 4 and 6 mm from the apex for stereomicroscope and confocal laser scanner microscopy (CLSM) analysis. In addition, 30 bovine incisors were contaminated with Enterococcus faecalis and divided into 3 groups (n = 10). The specimens were obturated by using the single cone technique with (G1) and without (G2) UA of the sealer and G3 as the control group. All were sectioned into 6 mm-long cylinders and stained with LIVE/DEAD to assess bacterial viability by CLSM. Results: The UA of the sealer significantly reduced the presence of unfilled areas in the canal and isthmus area in all sections (p